INTERCROPPING OF MEDICINAL PLANTS - Singh D.C.; Sharma Ashwini Kumar; Vashisht Kiran. (International Journal of Applied Ayurved Research, 2015)
Medicinal and Aromatic plants are upstream elements of food, flavor and cosmetic industries. These plants can be cultivated in order to obtain essential oils and fragrant chemical for commercial use. The demand for Medicinal and Aromatic plants is increasing day by day at national as well as international markets and in Ayurvedic preparations medicinal plants are mainly used and are in short supply from traditional source. Therefore intercropping of medicinal plants shall be advocated and adopted for obtaining additional remuneration for the farmers. Medicinal plants like Lavendulaofficinalis, Atropa belladonna and Echinacea purpurea are important source of alkaloids and essential oils, which have huge demand in pharmaceutical industries. The wide spacing available in the tree type of plantation facilitates the cultivation of Medicinal plants as an intercrop because utilization of Medicinal plants as an intercrop with other plant to generate an additional income to farmers.